2015
DOI: 10.2478/johr-2015-0019
|View full text |Cite
|
Sign up to set email alerts
|

Influence Of Chemicals Of Arbolin Group On Branching Of Maiden Trees Of Three Apple Cultivars

Abstract: Studies realized in 2008 and 2009 proved that Neo Arbolin Extra (10 g GA4+7 and 50 g BA in 1 l of solution) and Neo Arbolin (18 g GA4+7 and 18 g BA in 1 l of solution) applied separately or with Algamino Plant (18% extract from seaweeds and 10% of potassium salt of amino acids) stimulated the development of axillary buds on apple maiden trees of ‘Ligol’, ‘Golden Delicious’ and ‘Mutsu’ cultivars grafted on M.9 rootstock, thus enhancing the number of feathers longer than 10 cm. Preparations were applied twice, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The architecture and structures of fruit trees influence the resultant crop efficiency and productivity, which is a foremost selection criterion for fruit breeders [176]. Lateral branch development has been reported to be beneficial for increasing the bearing surface and in promoting the early production in horticultural fruits such as apple and the sweet cherry tree [37,[177][178][179][180]. Different approaches are often devised to manipulate the structure of a fruit tree for improved performance and productivity [178,179,181].…”
Section: General Growth and Health Of Fruit Crops/treesmentioning
confidence: 99%
See 1 more Smart Citation
“…The architecture and structures of fruit trees influence the resultant crop efficiency and productivity, which is a foremost selection criterion for fruit breeders [176]. Lateral branch development has been reported to be beneficial for increasing the bearing surface and in promoting the early production in horticultural fruits such as apple and the sweet cherry tree [37,[177][178][179][180]. Different approaches are often devised to manipulate the structure of a fruit tree for improved performance and productivity [178,179,181].…”
Section: General Growth and Health Of Fruit Crops/treesmentioning
confidence: 99%
“…The effectiveness of combining CKs with other PGRs, especially GA, has been explored by researchers [177,183]. As demonstrated by Zhalnerchyk et al [180], Neo Arbolin and Neo Arbolin Extra (commercial branching products consisting of BA and GA) stimulated varying degrees of branching in three apple cultivars. Four variants of Arbolin, with differing compositions of BA and GA, effectively promoted laterals in difficult-to-branch apple cultivars [183].…”
Section: General Growth and Health Of Fruit Crops/treesmentioning
confidence: 99%
“…BA is used as a branching agent in nurseries and young orchards (Cline and Dong, 2002). Zhalnerchyk et al (2015) suggested that the increase in branches number as a result of BA application could be attributable to its impact on counteraction or elimination of apical dominance and stimulate the lateral branching development. The apical dominance and branching, as reported by Sachs and Thimann (1967), depend on the concentration of auxine commonly secreted by the apex, and cytokinine provided by the inhibited organ.…”
Section: Number Of Nodes Per Branchmentioning
confidence: 99%